2022
DOI: 10.1038/s41392-022-00952-w
|View full text |Cite
|
Sign up to set email alerts
|

Hymecromone: a clinical prescription hyaluronan inhibitor for efficiently blocking COVID-19 progression

Abstract: Currently, there is no effective drugs for treating clinically COVID-19 except dexamethasone. We previously revealed that human identical sequences of SARS-CoV-2 promote the COVID-19 progression by upregulating hyaluronic acid (HA). As the inhibitor of HA synthesis, hymecromone is an approved prescription drug used for treating biliary spasm. Here, we aimed to investigate the relation between HA and COVID-19, and evaluate the therapeutic effects of hymecromone on COVID-19. Firstly, HA was closely relevant to c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Hellman et al [ 13 ] reported that fatal cases of COVID-19 were associated with the accumulation of hyaluronic acid in the alveolar spaces of the lungs and occurrences of hypoxemia and respiratory failure. A mouse model has also been shown to develop lesions in the lungs due to HA[ 15 ]. In a prospective study, the authors found that the COVID-19 cytokine milieu stimulates aberrant synthesis and degradation of HA, and HA fragments present at elevated levels in COVID-19 patient plasma directly induce endothelial barrier dysfunction[ 16 ].…”
Section: Alterations In Ecm Molecules In Covid-19mentioning
confidence: 99%
“…Hellman et al [ 13 ] reported that fatal cases of COVID-19 were associated with the accumulation of hyaluronic acid in the alveolar spaces of the lungs and occurrences of hypoxemia and respiratory failure. A mouse model has also been shown to develop lesions in the lungs due to HA[ 15 ]. In a prospective study, the authors found that the COVID-19 cytokine milieu stimulates aberrant synthesis and degradation of HA, and HA fragments present at elevated levels in COVID-19 patient plasma directly induce endothelial barrier dysfunction[ 16 ].…”
Section: Alterations In Ecm Molecules In Covid-19mentioning
confidence: 99%
“…We have confirmed that hymecromone could inhibit hyaluronan production in HEK293T and MRC5 cells 4 , thereby demonstrating its potential to treat COVID-19 by reducing hyaluronan. Through a subsequent clinical trial, we also found that hymecromone could improve clinical manifestations (such as lymphopenia and pulmonary lesions) 9 . Assuredly, many more lives could be saved if the efficacy of hymecromone against COVID-19 is confirmed in a larger sample.…”
Section: Hymecromone Could Be An Oral Prescribed Drug To Fight Agains...mentioning
confidence: 70%
“…Furthermore, since hyaluronan is closely associated with currently known indicators (such as C-reactive protein, and lymphocytes) of COVID-19 progression 9 , it may also be used to distinguish different stages of COVID-19. The recent appearance of the Omicron variant has resulted in many asymptomatic infections of SARS-CoV-2 worldwide.…”
Section: Hyaluronan Is a Promising Biomarker For The Progression Of C...mentioning
confidence: 99%
“…The small HA fragments bound to their receptors CD44 and layilin to activate the Rho-associated protein kinase (ROCK) signaling pathway, which were known to disrupt the endothelial barrier integrity [ 106 ]. Hymecromone, a synthetic inhibitor of HA, has been shown to improve lymphopenia and lung lesions, promoting the recovery of clinical manifestations in SARS-CoV-2-infected patients [ 127 ]. These studies indicated the role for HA in the vascular pathology of COVID-19, and more components that induce endothelial dysfunction need to be further confirmed.…”
Section: The Mechanisms Of Covid-19-induced Endothelial Glycocalyx Da...mentioning
confidence: 99%